2021
DOI: 10.4025/actasciagron.v43i1.53317
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and genetic divergence among tropical maize inbred lines using SSR markers

Abstract: Our objectives were to evaluate general and specific combining ability (SCA) and genetic divergence among tropical maize inbred lines using single sequence repeat (SSR) markers. Thirteen inbred lines were crossed based on a complete diallel scheme. Hybrids and three checks were evaluated in a lattice experimental design. Silk and anthesis flowering, average plant height, average ear height, white spot (Pantoea ananatis) and gray leaf spot (Cercospora zeae-maydis) severity, and grain yield were evaluated. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(56 reference statements)
4
2
0
Order By: Relevance
“…Finally, the result is in line with several researchers report. Accordingly, the result of this finding agrees with [36,18,13,31,10,35,9] they were found positive and negative significant GCA effect for the same traits.…”
Section: General Combining Ability Effect Estimatessupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the result is in line with several researchers report. Accordingly, the result of this finding agrees with [36,18,13,31,10,35,9] they were found positive and negative significant GCA effect for the same traits.…”
Section: General Combining Ability Effect Estimatessupporting
confidence: 91%
“…On other hand, L6, L9, T3 and T4 were showed significantly negative GCA effects for GY, indicating, that these inbred lines and testers were not good combiner within this group of inbred lines and may not be exploited for GY advancement. Matched with the current study, several authors reported either positive or negative significant GCA effects of inbred lines for GY in other group of inbred lines [31,10,27,9] . For ASI, all lines and testers showed negative and positive nonsignificant GCA effects.…”
Section: General Combining Ability Effect Estimatessupporting
confidence: 67%
“…On other hand, L6, L9, T3 and T4 were showed significantly negative GCA effects for GY, indicating, that these inbred lines and testers were not good combiner within this group of inbred lines and may not be exploited for GY advancement. Matched with the current study, several authors reported either positive or negative significant GCA effects of inbred lines for GY in other group of inbred lines [31,10,27,9] . For ASI, all lines and testers showed negative and positive nonsignificant GCA effects.…”
Section: General Combining Ability Effect Estimatessupporting
confidence: 64%
“…Maize (Zea mays L.) is playing main role in human and livestock nutrition worldwide and is used for several industrial purposes such as oil and starch [11]. Internationally, maize is known as queen of cereals because of its highest genetic yield potential.…”
Section: Introductionmentioning
confidence: 99%